Spirituality wellbeing among Malaysian youth - Dahalan, Dzuhailmi; D’Silva, Jeffrey Lawrence; Abu Samah, Asnarulkhadi; Mohamed, Nor Aini; Mohamed Shaffril, Hayrol Azril (Allied Business Academies, 2019)
This article examines spiritual well-being among Malaysian youth. The findings presented are a small part of the overall research data on Malaysian youth well-being. This is a quantitative study involving a total of 500 respondents aged 19-30 years from the five zones in Malaysia. Overall, the results depict that youth have a high level of spiritual well-being. Further findings show that there was a significant difference in spiritual well-being based on location, gender, and zones. Even though the study did not examine the relationship between youth spiritual well-being and quality of life, the study recommends that the spiritual well-being of youth need to be given immense attention by all concerned parties based on the mounting challenging environment youths are in.